2021
DOI: 10.24075/brsmu.2021.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the novel coronavirus infection COVID-19 on the mother-placenta-fetus system

Abstract: Impaired placental development during early pregnancy associated with systemic damage to the vascular endothelium in patients with COVID-19 may result in a number of complications. The study was aimed to reveal histological and immunohistochemical (IHC) features of placental tissue in pregnant women with COVID-19 at different stages of gestation, and to examine the contribution of those to pathogenesis of the disease involving mother-placenta-fetus system. The following two groups of pregnant women were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several studies have reported similar findings associated with SARS-CoV-2 infection [24,25]. These findings indicate a placental inflammatory process related to viral invasion, potentially increasing the likelihood of severe maternal and fetal outcomes [33,34]. However, further research is required to establish a direct association with disease severity or progression, particularly concerning transplacental transmission and considering gestational age at the time of infection [35].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several studies have reported similar findings associated with SARS-CoV-2 infection [24,25]. These findings indicate a placental inflammatory process related to viral invasion, potentially increasing the likelihood of severe maternal and fetal outcomes [33,34]. However, further research is required to establish a direct association with disease severity or progression, particularly concerning transplacental transmission and considering gestational age at the time of infection [35].…”
Section: Discussionmentioning
confidence: 67%
“…However, the association with maternal or fetal vascular changes remains unclear, as some studies reported similar odds of vascular changes between SARS-CoV-2 infected and healthy individuals [32]. In contrast, others reported increased arteriopathies, hypercapillarization, or villous tree immaturity [33]. In a few cases, these changes were associated with chronic histiocytic intervillositis, membrane hemorrhage, poor placental vascular perfusion, and an increase in perivillous fibrin deposition on the maternal side and occasionally severe outcomes such as fetal death [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the neutrophil to macrophage ratio is much higher in early, localized placentitis as compared to diffuse infection [ 33 ]. Infection is also associated with increased levels of inflammatory cytokines including interferon stimulated genes (IFI6, OAS1, CCL3) and proteins (IFNa, IFNy, CCL4), interleukin-10 (IL-10) expression [ 21 ], CXC-motif chemokine ligand 10 (CXCL10) [ 18 , 25 ], tumor necrosis factor alpha (TNFa), CXC-motif chemokine ligand 8 (CXCL8) [ 32 ], interferon gamma-induced protein 10 (IP-10), interferon gamma/ monokine induced by interferon-gamma IFNy/MIG [ 41 ], C-C motif chemokine ligand 3 and 5 (CCL3, CCL5), interleukin-6 (IL-6), interleukin-1-beta (IL1B), interferon alpha (IFNa), and interferon beta (IFNB) [ 35 ] and a decrease in interleukin-4 (IL-4) and macrophage migration inhibitory factor (MIF) expression [ 32 ]. Infection was also associated with an increase in host antiviral effector gene expression including MX dynamin like GTPase 1 (MX1), interferon induced transmembrane protein 1 and 3 (IFITM1, IFITM3), cholesterol 25-hydroxylase (CH25H), toll-like receptor 3 (TLR3), and DExD/ H-box helicase 58 (DDX58) [ 35 ], and increased expression of genes and pathways involved in inflammatory response to viral infection [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive intervillous fibrin deposition, involving up to 70% or more of the placental tissues in one case, was present in the placentas from all 5 fetuses. Following this report, additional case reports of the placental pathology from stillborn fetuses delivered to mothers with COVID-19 were reported that showed all the placentas to be markedly abnormal and extensively involved with similar destructive features–increased or massive intervillous fibrin deposition, villous trophoblast necrosis, and chronic histiocytic intervillositis [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In their report of a stillbirth from a mother having COVID-19 at 30 weeks 4 days gestation in Bratislava, Biringer et al [ 80 ] believed the cause of death to be acute placental insufficiency based upon their findings of placental destruction due to SARS-CoV-2 placentitis and an autopsy revealing fetal organs to have no morphological abnormalities.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 97%
“…The authors stated that the placental abnormalities were consistent with intense vascular malperfusion which likely resulted in fetal death. A report from Russia described an immunocompromised mother with acute leukemia who developed COVID-19 and delivered a stillborn fetus at 20 weeks of gestation in which there was extensive placental damage causing placental insufficiency and fetal death [ 87 ].…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%